1994
DOI: 10.1038/jcbfm.1994.84
|View full text |Cite
|
Sign up to set email alerts
|

The Brain at High Altitude: Hypometabolism as a Defense against Chronic Hypoxia?

Abstract: Summary: The brain of hypoxia-tolerant vertebrates is known to survive extreme limitations of oxygen in part because of very low rates of energy production and utili zation. To assess if similar adaptations may be involved in humans during hypoxia adaptation over generational time, volunteer Quechua natives, indigenous to the high Andes between about 3,700 and 4,900 m altitude, served as subjects in positron emission tomographic measure ments of brain regional glucose metabolic rates. Two met abolic states wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
2
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 32 publications
6
63
2
1
Order By: Relevance
“…Of the above O 2 sensor-linked response systems, for example, the blunting of HVR in Quechuas (40) and Sherpas (41) and the increase in RBC mass in Andeans (7,(14)(15)(16) are more robust than in Tibetans (40). Similarily, glucose metabolic rates are downregulated mildy in the central nervous system in Quechuas, hypometabolism seemingly being used as an hypoxia defense strategy (13), but this trait is not expressed in Sherpas (14). Such differences in some physiological characters are not unexpected, given the length of time these lineages have been evolving separately (see below), and they do not alter our impression of a high altitude physiological phenotype based on many similar traits in Quechuas and Sherpas.…”
Section: Physiology: Hochachka Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Of the above O 2 sensor-linked response systems, for example, the blunting of HVR in Quechuas (40) and Sherpas (41) and the increase in RBC mass in Andeans (7,(14)(15)(16) are more robust than in Tibetans (40). Similarily, glucose metabolic rates are downregulated mildy in the central nervous system in Quechuas, hypometabolism seemingly being used as an hypoxia defense strategy (13), but this trait is not expressed in Sherpas (14). Such differences in some physiological characters are not unexpected, given the length of time these lineages have been evolving separately (see below), and they do not alter our impression of a high altitude physiological phenotype based on many similar traits in Quechuas and Sherpas.…”
Section: Physiology: Hochachka Et Almentioning
confidence: 99%
“…As in the pinniped example, current evidence indicates that ''conservative'' and ''adaptable'' physiological characters are involved in human responses to hypoxia. Because now we are dealing with traits within a single species, conservative characters clearly are dominant and are too numerous to outline in detail; three examples are Hb O 2 affinity and regulation (36), muscle organization into different fiber types (11,38,39), and the region-specific organization of brain metabolism with the brain's almost exclusive preference for glucose as a fuel (13,14). These kinds of physiological traits-which in sum make up most of our physiology-appear to be conserved through phylogenetic time by negative selection, and the ways they are used on hypoxia exposure appear common in humans no matter what the O 2 content of the inspired air in the normal environment.…”
Section: Fig 2 (A)mentioning
confidence: 99%
“…In addition to brain hypometabolism (Hochachka et al. 1994; Richardson et al. 2011), neuroimaging studies in recent years have revealed compensatory processes for brain structure and function in indigenous residents and immigrants who were born and raised in HA (Yan et al.…”
Section: Introductionmentioning
confidence: 99%
“…High-altitude (HA) natives have developed distinctive biologic characteristics in respiratory and circulatory functions, 1,2 hemoglobin concentration, 3 arterial oxygen saturation, 4 energy metabolism, 5 and genes 6 to offset the stresses of HA environmental factors. Previous studies have revealed the adaptation of the cerebral glucose metabolic rate 7 in HA Quechua natives and the adaptation of cerebral autoregulation in HA Himalayan natives 8 and Ethiopian natives. 9 However, existing studies provided no assessments of the cerebral structures in HA natives.…”
mentioning
confidence: 99%